Fatores de risco nutricionais associados à mortalidade em pacientes com lesão renal aguda de acordo com os critérios do Acute Kidney Injury Network (AKIN) - Pinto, Milene Peron Rodrigues [UNESP] (2015)
The Acute Kidney Injury (AKI) is characterized as rapid clinical deterioration associated with the syndrome of renal function, and is considered an independent risk factor for mortality. The current definition classifies the LRA according to the stages of AKIN, 1 (equivalent to risk), 2 (injury) and 3 (bankruptcy). In the literature there are few studies evaluating the differences between the patients of these stages and those existing reveal changes both in nutritional parameters as mortality rates, making it important to check the risk factors at each stage of the LRA. The objectives of this study were from the first nutritional assessment, identify and compare the nutritional risk factors associated with death in patients with AKI stratified by AKIN. It was prospective cohort performed at the Hospital of the Faculty of Medicine of Botucatu - UNESP within 24 consecutive months. Soon after the first evaluation nephrology, patients were classified according to the criteria of AKIN in 3 stages and was conducted a nutritional assessment made by clinical, anthropometric data, food intake, nitrogen balance, bioimpedance, Subjective Global Assessment (SGA) and examinations laboratory, with the outcome death. We evaluated 471 patients, predominantly male and older than 60 years, with mortality of 43.5%. Of the patients studied, 12.9% presented with a AKIN LRA-1, 39.9% with AKIN-2 and 47.2% with AKIN-3. After multivariate analysis, the variables that were related to higher mortality in patients with AKIN-1foram sepsis and SGA class C (mild malnutrition / moderate), with AKIN-2 older than 60 years, ICU stay, presence of oliguria and lower nitrogen balance values and AKIN-3 smaller follow-up by a nephrologist, age greater than 60 years, ICU stay, sepsis, fasting, lower levels of total cholesterol and increased edema value for Watson. In conclusion, from the initial nutritional assessment, it was possible to identify risk factors associated with ...